2017
DOI: 10.24953/turkjped.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of Kawasaki disease presented with acute febrile jaundice

Abstract: Kawasaki disease is an acute, systemic vasculitis of unknown etiology. Although gastrointestinal involvement does not belong to the classic diagnostic criteria; diarrhea, abdominal pain, hepatic dysfunction, hydrops of gallbladder, and acute febrile cholestatic jaundice are reported in patients with Kawasaki disease. We describe here two cases presented with fever, and acute jaundice as initial features of Kawasaki disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…This case and others emphasize the importance for emergency physicians to retain a high level of suspicion for KD when a child presents with febrile or afebrile obstructive jaundice. [7][8][9][10][11][12][13][14][15] Documented patient informed consent and/or Institutional Review Board approval has been obtained and filed for publication of this case report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This case and others emphasize the importance for emergency physicians to retain a high level of suspicion for KD when a child presents with febrile or afebrile obstructive jaundice. [7][8][9][10][11][12][13][14][15] Documented patient informed consent and/or Institutional Review Board approval has been obtained and filed for publication of this case report.…”
Section: Discussionmentioning
confidence: 99%
“…We identified nine previous case reports, with a total of 17 KD patients displaying jaundice. [7][8][9][10][11][12][13][14][15] Although rarely reported, KD is the most common cause of glutamyltransferase was elevated at 241U/L (15-73 U/L). Throat cultures, antistreptolysin O, hepatitis B surface antigen, hepatitis B core antibody, hepatitis A immunoglobulin (Ig) M, hepatitis C antibody, cytolomegalo virus IgG/IgM, toxoplasmosis IgG/IgM, monospot, blood cultures, and leptospirosis testing were negative, making infectious or post-infectious etiologies less likely.…”
Section: Image 1 Erythematous Tongue With Papules On Day Of Emergency Department Presentation (Day 4 Of Illness)mentioning
confidence: 99%
“…KD may present with uncommon symptoms such as pneumonia, pleural effusion, diarrhea, vomiting, sterile pyuria, gallbladder hydrops, acute cholestatic hepatitis, arthritis, and aseptic meningitis [27]. Pulmonary system involvement of KD is very rare; KD can present as pneumonia, pulmonary nodules, bronchopneumonia, hydropneumothorax, and pleural effusion [6, 8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study of 23 patients, hydrops of gallblader was reported in 1 case and transaminase elevation in 7 cases [ 7 ]. Kaman et al also reported 2 cases of atypical kawasaki disease with acute febrile jaundice [ 8 ].…”
Section: Discussionmentioning
confidence: 99%